The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1037/xge0000565
|View full text |Cite
|
Sign up to set email alerts
|

Simulating other people changes the self.

Abstract: The self is not static. Our identities change considerably over development and across situations. Here, we propose one novel cause of self-change: simulating others. How could simply imagining others change the self? First, when simulating other people's mental states and traits, individuals access self-knowledge; they do so while concurrently considering information about the other person they are trying to understand. Second, episodic and semantic knowledge is malleable and susceptible to incorporating new,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 88 publications
(139 reference statements)
6
20
0
Order By: Relevance
“…Studies 1-2 show that when simulation involves episodic memories, simulation of another individual can be incorporated into episodic memories, altering self-knowledge beyond what working self-concept can account for. Though episodic and semantic self-knowledge are distinct, prior work on SIM suggests that trait-related self-knowledge is vulnerable to change based on simulation, just like other types of knowledge (Klein et al, 1999;Klein & Lax, 2010;Meyer et al, 2019). When participants simulate another individual by rating how well traits apply to them, their ratings of how well those traits apply to themselves change in the direction of the target.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies 1-2 show that when simulation involves episodic memories, simulation of another individual can be incorporated into episodic memories, altering self-knowledge beyond what working self-concept can account for. Though episodic and semantic self-knowledge are distinct, prior work on SIM suggests that trait-related self-knowledge is vulnerable to change based on simulation, just like other types of knowledge (Klein et al, 1999;Klein & Lax, 2010;Meyer et al, 2019). When participants simulate another individual by rating how well traits apply to them, their ratings of how well those traits apply to themselves change in the direction of the target.…”
Section: Methodsmentioning
confidence: 99%
“…Participants (N=186) were recruited from Prolific. This sample size provided at least 99% power to detect a target x time interaction effect, at a size reported by prior work on this same effect (Meyer et al, 2019). Participants were excluded prior to analyses based on three a priori exclusion criteria: if they completed the task in an unreasonably short period of time (n = 2), if they self-reported poor English proficiency, or if they provided fewer than 15 unique answers.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, ventromedial prefrontal cortex and temporoparietal junction are implicated in self/other processing and judgments (Denny et al, 2012 ) and it has been suggested that overcoming self–other interference and ToM are deeply integrated processes (Qureshi et al, 2020 ). Moreover, simulating others has been shown to influence self-knowledge, with trait and memory measures becoming similar to a simulated other after adopting their perspective (Meyer et al, 2019 ). In relation to acting, a recent neuroimaging study demonstrated that when trained actors answered questions from the first-person fictional perspective of a character, in contrast to their own perspective, dorsomedial prefrontal cortex/superior frontal gyrus and ventromedial prefrontal cortex are deactivated, suggesting acting may involve the suppression of self-processing (Brown et al, 2019 ).…”
Section: Theory Of Mind and Empathymentioning
confidence: 99%